Rancang Bangun End-Effector Pada Robot Pemetik Buah Tomat Berbasis Raspberry Pi 3 Model B+ - Purwiyanti, Sri; Ali, Ibrahim; sumadi, Sumadi; Setyawan, FX. Arinto (JURNAL SURYA ENERGY, 2020)
In this modern era, technology is used to facilitate human activities in various fields, as well as in agriculture. This study aims to design an end-effector of  robotic arm to assist the tomato harvesting process. Thus, it can enable farmers to get good quality crops and is more efficient in terms of time and human labor. The robot is built using a camera to detect and determine the position of ripe tomatoes, then the data information is forwarded to the raspberry pi which will process the data. Based on the data received, the raspberry pi then sends a signal that will regulate the movement of the horizontal servo motor, vertical servo, forward servo, and gripper servo to move according to the coordinates of the tomato position. Based on test data, it is found that this robot is able to work well at a distance between 14 cm to 20 cm with a height between 10 cm to 21 cm and a light intensity of 164 Lux.